VMware horizon 6 desktop virtualization solutions : plan, design, and secure your virtual desktop environments with VMware horizon 6 view /: plan, design, and secure your virtual desktop environments with VMware horizon 6 view. (2014) - Cartwright, Ryan (Ryan P.)
No abstract available